Characterization and Targeted Disruption of Murine Nup50, a p27(Kip1)-Interacting Component of the Nuclear Pore Complex - Smitherman, Matthew (American Society for Microbiology, 2000)
p27(Kip1) is a member of the Cip-Kip family of cyclin-dependent kinase (Cdk) inhibitors that binds to cyclin-Cdk complexes and inhibits their catalytic activity in response to antiproliferative stimuli. p27(Kip1) is regulated by several posttranscriptional mechanisms, including subcellular localization. We have identified a component of the nuclear pore complex (NPC), termed Nup50, through its two-hybrid interactions with p27(Kip1). Nup50 is a nucleoplasmically oriented component of the nuclear pore complex with a role in protein export (T. Guan, R. H. Kehlenbach, E. C. Schirmer, A. Kehlenbach, F. Fan, B. E. Clurman, N. Arnheim, and L. Gerace, Mol. Cell. Biol. 20:5619–5630, 2000). We found that murine Nup50 is a widely expressed nucleoporin and that Nup50 expression is highest in the developing neural tube and adult testes. We have also examined interactions between Nup50 and the NPC and found specific two-hybrid interactions between Nup50 and several well-defined components of the NPC, as well as coimmunoprecipitation of Nup50 with the nucleoporin Nup153 from transfected mammalian cells. In order to study Nup50 function in vivo, we cloned the mouse Nup50 genomic locus and created a targeted Nup50 deletion in the mouse germ line. Nup50 disruption resulted in a complex phenotype characterized by late embryonic lethality, neural tube defects, and intrauterine growth retardation. Although Nup50-null mouse embryo fibroblasts exhibited no defects in either cell cycle control or p27(Kip1) regulation, Nup50 deletion was associated with abnormalities in p27(Kip1) expression and cell proliferation in the developing neuroepithelium. We conclude that Nup50 is a nucleoporin with essential functions during mouse development.